Dynamic of the content of radionuclides in water of cooling-pond of Chernobyl NPP (1978 - 2004) - O. L. Zarubin (Ядерна фізика та енергетика)
Dynamic of the artificial radionuclides content of in water of the cooling-pond of ChNPP was studied starting from 1978 till 2004. The total content of radionuclides was founded within the limits of 0,005 - 0,05 Bq/l in the period of 1978 - 1984. After the accident in 1986 the total content of radionuclides in water amounted to 3,7 ⋅ 105 Bq/l. The main contribution in radionuclides’ pollution of water introduces 137Cs and 90Sr from the end of 1986. Their content is sharply decreased till 1990 - 1992, and then the decrease occurs more smoothly. Seasonal dynamic of the content of 137Cs is revealed. In by autumn its quantity in water is increased. The abnormal low relation 90Sr/137Cs in water of cooling-pond on comparison with other reservoirs 30-km Zone is registered during 1987 - 2004. The content of radionuclides in water of the cooling-pond of ChNPP in 2004 approximately in 100 times exceeds the levels of content before the accident.